2015
DOI: 10.1021/acs.jpcc.5b00560
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Orientation and Binding Motifs of Lysozyme and Chymotrypsin on Amorphous Silica

Abstract: The adsorption of α-chymotrypsin and hen egg white lysozyme on amorphous silica is studied by molecular dynamics (MD) simulations in comparison with adsorption experiments. Protein–surface interaction profiles are computed in implicit solvent at the level of DLVO theory. These reveal a preferential adsorption orientation for chymotrypsin, driven by its large dipole moment, with its α-helical regions pointing toward the surface. Instead, a less clear orientational preference characterizes lysozyme adsorption, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 52 publications
5
59
1
Order By: Relevance
“…It is worthwhile to compare the results in Figure 4 with the predictions of constant-charge MD simulations in literature, which modelled the adsorption of lysozyme on negatively charged silica surfaces at pH 7 49,50 and 8. 51 The orientation predicted by our model for lysozyme at its isoelectric point (pH 11.2) on a negative surface is very close to the most stable orientation predicted by these MD simulations. [49][50][51][52] Moreover, MD studies have identified the same aminoacids as our study (Lys1, Arg5, Arg125 and Arg128) as the aminoacids that reside closest to the surface and contribute the most to the interaction with the silica substrate.…”
Section: Analysis Of Lysozyme-surface Interactionsupporting
confidence: 77%
“…It is worthwhile to compare the results in Figure 4 with the predictions of constant-charge MD simulations in literature, which modelled the adsorption of lysozyme on negatively charged silica surfaces at pH 7 49,50 and 8. 51 The orientation predicted by our model for lysozyme at its isoelectric point (pH 11.2) on a negative surface is very close to the most stable orientation predicted by these MD simulations. [49][50][51][52] Moreover, MD studies have identified the same aminoacids as our study (Lys1, Arg5, Arg125 and Arg128) as the aminoacids that reside closest to the surface and contribute the most to the interaction with the silica substrate.…”
Section: Analysis Of Lysozyme-surface Interactionsupporting
confidence: 77%
“…Key questions that still need to be addressed concern not only the extent of protein adsorption, i.e. whether complete surface coverage or even multilayer coverage is achieved, but also the strength of the adhesion to the surface and the functionality of the adsorbed protein [9][10][11][12][13][14] . These factors directly the affect the utility of the adsorbed proteins for functionalization of surfaces to induce biocompatibility, create antibacterial coatings, or yield novel nanoparticulate drug delivery systems 1 .…”
Section: Introductionmentioning
confidence: 99%
“…We found a near‐symmetrical energy barrier of ≈0.3 eV for rotation of the molecule on graphene between edge‐on and end‐on Fc binding modes. This rotational barrier is almost identical to that computed for model proteins interacting with silica substrates, and is half of that calculated between hydrocarbon dimers . Fokin et al also verified that the Perdew–Burke–Ernzerhof (PBE) functionals outperform the majority of hybrid functionals as regards matching experimental energy barrier data.…”
mentioning
confidence: 52%